2021
DOI: 10.4049/jimmunol.2100649
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Monocytes Respond to Cell-Free Fetal DNA and Initiate Key Processes of Human Parturition

Abstract: Throughout gestation, the maternal immune system is tightly modulated to allow growth of a semiallogeneic fetus. During the third trimester, the maternal immune system shifts to a proinflammatory phenotype in preparation for labor. What induces this shift remains unclear. Cell-free fetal DNA (cffDNA) is shed by the placenta and enters maternal circulation throughout pregnancy. Levels of cffDNA are increased as gestation progresses and peak before labor, coinciding with a shift to proinflammatory maternal immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…It is known that cffDNA can stimulate inflammation in several tissues and cell types ( Goldfarb et al, 2018 ; Kazemi et al, 2021 ; Yeganeh Kazemi et al, 2021 ) but its effects have not yet been studied on the human FM. In addition to this, it is also known that the sex of the fetus can influence both the magnitude and the resultant cytokine profile of the inflammatory response, depending on the specific circumstances ( Burns et al, 2015 ; Mitchell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that cffDNA can stimulate inflammation in several tissues and cell types ( Goldfarb et al, 2018 ; Kazemi et al, 2021 ; Yeganeh Kazemi et al, 2021 ) but its effects have not yet been studied on the human FM. In addition to this, it is also known that the sex of the fetus can influence both the magnitude and the resultant cytokine profile of the inflammatory response, depending on the specific circumstances ( Burns et al, 2015 ; Mitchell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating levels of cffDNA have also been associated with adverse pregnancy outcomes and pathologies such as; preeclampsia ( Martin et al, 2014 ; Kwak et al, 2020 ), gestational diabetes ( Hopkins et al, 2020 ), and preterm birth ( Gomez-Lopez et al, 2020 ). cffDNA from the trophoblast is also known to increase by sterile inflammation, via HMGB1 ( Yaganeh Kazemi et al, 2021 ), but its ability to generate inflammation itself is contentious. Some studies have clearly shown that it is able to interact with toll-like receptor 9 (TLR9) ( Goldfarb et al, 2018 ) and that immune cells respond to it by producing inflammatory cytokines ( Yeganeh Kazemi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms by which pregnancy-induced monocyte functional changes are unknown. It has been suggested that the factors released by trophoblasts such as cytokines [ 8 ], fetal DNAs [ 9 ], or hormones contribute to the changes in monocytes [ 6 ]. Extracellular vesicles are a newly found mode of intercellular communications.…”
Section: Introductionmentioning
confidence: 99%
“…Successful pregnancy is associated with the functional regulation of monocytes [ 9 , 11 ]. We hypothesized that the pEXO facilitates the establishment of maternal immune tolerance via regulating monocyte phenotype in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%